2013
DOI: 10.1021/bm400619v
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Ligand Density on Intravenous Hemostatic Nanoparticles Dramatically Increases Survival Following Blunt Trauma

Abstract: Targeted nanoparticles are being pursued for a range of medical applications. Here, we utilized targeted nanoparticles (synthetic platelets) to halt bleeding in acute trauma. One of the major questions that arises in the field is the role of surface ligand density on targeted nanoparticles’ performance. We developed intravenous hemostatic nanoparticles (GRGDS-NP1), and previously demonstrated their ability to reduce bleeding following femoral artery injury and increase survival after lethal liver trauma in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 47 publications
10
60
0
Order By: Relevance
“…We found that 9.3% of the injected dose of the hemostatic nanoparticles was recovered at 1 h, which is consistent with the clearance seen in our previous work (18,20). The majority of the particles (5.2% for hemostatic nanoparticles and 4.7% for control nanoparticles) were found in the lungs, a major site of bleeding for this type of injury (Fig.…”
Section: Role Of Hemostatic Nanoparticles On Lung Injury Following Blastsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that 9.3% of the injected dose of the hemostatic nanoparticles was recovered at 1 h, which is consistent with the clearance seen in our previous work (18,20). The majority of the particles (5.2% for hemostatic nanoparticles and 4.7% for control nanoparticles) were found in the lungs, a major site of bleeding for this type of injury (Fig.…”
Section: Role Of Hemostatic Nanoparticles On Lung Injury Following Blastsupporting
confidence: 90%
“…PLGA-PLL-PEG-GRGDS block copolymer for the hemostatic nanoparticles and PLGA-PLL-PEG-GRADSP were synthesized using protocols described previously (18)(19)(20). In brief, the triblock polymer was synthesized using stepwise conjugate reactions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations